2004
DOI: 10.1253/circj.68.1127
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cigarette Smoking-Induced Hemodynamic Alterations in the Common Carotid Artery-A Transcranial Doppler Study-

Abstract: moking is known as a major risk factor in the development and progression of cardiovascular disease; 1 but despite extensive research, the pathophysiological mechanisms that are responsible for smoking-related vascular damage have not been elicited. In addition to alterations in hemostatic factors, endothelial function and blood lipids, the dynamic properties of the arterial wall may play an important role. 2 There is evidence that the compliance of both large and medium-sized arteries decreases immediately af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 39 publications
3
18
2
2
Order By: Relevance
“…11,27,28 Both passive and active smoking causes endothelial dysfunction. 8,29,30 In contrast to previous studies we found no relationship between smoking and endothelial dysfunction; however, almost all of the present patients had quit smoking after clinical and/or angiographic diagnosis of CAD. Benjamin et al 10 found that FMD% was better in smokers who did not smoke within the 6 h prior to the study hours than in those who did smoke.…”
Section: Discussioncontrasting
confidence: 99%
“…11,27,28 Both passive and active smoking causes endothelial dysfunction. 8,29,30 In contrast to previous studies we found no relationship between smoking and endothelial dysfunction; however, almost all of the present patients had quit smoking after clinical and/or angiographic diagnosis of CAD. Benjamin et al 10 found that FMD% was better in smokers who did not smoke within the 6 h prior to the study hours than in those who did smoke.…”
Section: Discussioncontrasting
confidence: 99%
“…The data showed a strong linear association between the duration of smoking and the percentage of carotid stenosis, which increased 0.34% per year, as well as between the frequency of smoking and the degree of carotid narrowing, which increased 0.31% per unit frequency. These findings are consistent with those of Barutcu et al, 5 whose results based on transcranial Doppler measurements suggested that smoking causes acute hemodynamic alterations in the common carotid artery. The data presented also agree with those of Tell et al, 6 who showed that among all participants, the prevalence of clinically significant (≥50%) internal carotid stenosis increased from 4.4% in never smokers to 7.3% in former smokers to 9.5% in current smokers (P < .0001).…”
Section: Discussionsupporting
confidence: 93%
“…The reason is multifactorial and may in part be associated with oxidative stress and systemic inflammation. In our study population, the patients in the lower FMD tertile were older, had higher BMI levels, and were more likely to have There are also many studies showing a connection between hypertension, elevated cholesterol levels, tobacco use, and endothelial function [26,33,34]. In our study, we did not find a relationship between those parameters and FMD, which might have resulted from the patients having appropriate antihypertensive, antihypercholesterolemic treatment and smoking cessation before FMD measurement.…”
Section: Discussioncontrasting
confidence: 54%